I Want to Know About: Horses - Elsa Z. Posell (Chicago Children's Press, 1981)
Briefly traces the growth and training of a foal, weanling, and yearling, discusses the history and uses of horses in America, and describes various kinds of horses.
Previously published as: The true book of horses. 1961.
Includes index. A new true book
Keywords: Encyclopedias (3GdehShYGJs; Horses -- Juvenile literature; General